(untitled) (Physical Education, Health and Social Sciences, 2025)
Students’ satisfaction has always been remained the center of educational achievement. Investigating the feelings of contentment with one’s academic achievements is crucial, as it provides deeper insights into students’ psychological well-being and long-term success, that how satisfaction influences motivation, resilience, and future aspirations among students. The objective of the study was to investigate the magnitude and direction of relationship between emotional intelligence and student’s satisfaction towards academic achievement and to analyze the magnitude of effect of the relationship between them. For this purpose, cross-sectional survey research was conducted on the university students of three renowned universities of South Punjab-Pakistan i.e. Bahauddin Zakariya University Multan, Islamia University Bahawalpur and Ghazi University, Dera Ghazi Khan. Total population of these universities was N= 43153. Sample size n=385 was determined through Krejcie and Morgan table (1970) for sample size determination. Data were collected through questionnaire based on socio-economic status and demographic profile, emotional intelligence scale by Bar-On (2006) and student satisfaction scale by Fieger (2012). Data were entered into SPSS-21 and basic profile was presented through frequency and percentage meanwhile the hypothetical model for association and effect were tested through Pearson Correlation Coefficient and Linear Regression model. Findings of the study a linear positive relationship between emotional intelligence and there was also significant effect of each predictor of emotional intelligence on the student’s satisfaction towards academic achievement. This study concluded that emotional intelligence plays a critical role in enhancing student satisfaction in education. By promoting better academic performance, effective stress management, and positive interpersonal relationships, EI contributes to a more fulfilling and successful educational experience.